Impact of Goods and Services Tax (GST) on the Financial Performance, Compliance Burden, Liquidity Management, and Operational Efficiency of Small and Medium Enterprises (SMEs) in Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper examines the effects of the Goods and Services Tax (GST) on small and medium-sized businesses (SMEs) in Madhya Pradesh in terms of their financial performance, legal practices, operational efficiency and growth opportunity. The research is based on secondary data collected through government reports, scholarly research, and industry reports aimed at testing the hypothesis of compliance burden, liquidity stress, and sector-specific issues. The major findings show that GST has put regressive compliance costs on average of 87,450 each year and an average of 372 administrative hours per SME, which is disproportionate on microenterprises due to complex rate classifications, delayed input tax credit (ITC), and cash-flow mismatches especially in agri-processing and manufacturing industries. Although ICT delays (73.7% overall) and confusion over classification (64.1%), which confirm hypotheses about issues in legal and financial barriers, are prevalent comparatively between sectors. Adaptive strategies, including digital invoicing, engagement with consultants, and contract renegotiations, which helped to avoid losses in profitability in the first place (e.g., 8% to 6% in retail), are documented in five case studies of Madhya Pradesh SMEs, but different strategies increased them over the long run. Although transparency and formalization have been improved by the unification of GST despite short term interference, the low use of exemptions (10.4) shows gaps in knowledge. The conclusion of the article is that GST presents serious operation challenges, but long term growth of the SMEs can be unlocked through focused policy simplifications which include slab mergers and quicker refunds. Suggestions focus on the digital literacy initiatives and industry-specific assistance to bring GST in line with the Indian entrepreneurial ecosystem.